Vitamin D immunoregulation through dendritic cells. Issue 3 (July 2016) - Bscheider, Michael; Butcher, Eugene C.
Summary: Vitamin D (VD3) has been linked to immunological processes, and its supplementation may have a role in treatment or prevention of diseases with underlying autoimmune or pro‐inflammatory states. As initiators of the immune responses, dendritic cells (DC) are a potential target of VD3 to dampen autoimmunity and inflammation, but the role of DC in VD3‐mediated immunomodulation in vivo is not understood. In addition to being targets of VD3, DC can provide a local source of bioactive VD3 for regulation of T‐cell responses. Here we review existing studies that describe the tolerogenic potential of VD3 on DC, and discuss them in the context of current understanding of DC development and function. We speculate on mechanisms that might account for the potent but poorly understood tolerogenic activities of VD3 and the role of DC as both targets and sources of this hormone.